THE IMPACT OF INFLUENCERS ON INDONESIAN GEN Z’s COSMETIC PURCHASE INTENTION THROUGH SOCIAL MEDIA - Cristina, Cristina; Nurjanah, Listia; Lady, Lady (Distribusi - Journal of Management and Business, 2025)
The rapid expansion of digitalization has transformed Indonesia into one of the world’s largest digital markets, with over 221 million internet users projected by 2024. This phenomenon has reshaped marketing strategies, particularly in the cosmetics industry, where influencers have emerged as central to engaging consumers. Generation Z (Gen Z), known as digital natives, represents a critical consumer segment due to their reliance on social media and preference for authentic, ethical, and relatable brand interactions. This study investigates the impact of influencer attributes attractiveness, expertise, and trustworthiness on Gen Z's purchase intention in Indonesia's cosmetics market, with a focus on the mediating roles of emotional attachment and brand trust. Using a quantitative research design, this study collected data through an online survey distributed to 302 Gen Z respondents who were social media users and had purchased cosmetics after viewing influencer recommendations. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships among variables. The findings reveal that while attractiveness indirectly influences purchase intention via emotional attachment and brand trust, expertise and trustworthiness have significant direct effects. Both emotional attachment and brand trust are identified as key mediators driving purchase behavior. These results highlight the importance of influencer credibility and emotional connections in shaping Gen Z's purchasing preferences. The study provides insights for marketers to optimize influencer-based strategies and emphasizes the need for future research to explore additional factors, such as brand reputation and customer satisfaction, in influencing Gen Z consumers.